2015
DOI: 10.1186/s12889-015-2669-2
|View full text |Cite
|
Sign up to set email alerts
|

Penile cancer treatment costs in England

Abstract: BackgroundPenile cancer is a rare malignancy in Western countries, with an incidence rate of around 1 per 100,000. Due to its rarity, most treatment recommendations are based on small trials and case series reports. Furthermore, data on the resource implications are scarce. The objective of this study was to estimate the annual economic burden of treating penile cancer in England between 2006 and 2011 and the cost of treating a single case based on a modified version of the European Association of Urology peni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…Penile cancer is a rare and devastating malignancy, with an incidence of approximately 1 per 100 000 1 . Men frequently present between the ages of 50 and 70 years old 2 and there has been an increased incidence in England over the last 30 years 3 …”
Section: Introductionmentioning
confidence: 99%
“…Penile cancer is a rare and devastating malignancy, with an incidence of approximately 1 per 100 000 1 . Men frequently present between the ages of 50 and 70 years old 2 and there has been an increased incidence in England over the last 30 years 3 …”
Section: Introductionmentioning
confidence: 99%
“…These procedures are associated with high psychological morbidity and negatively impact the quality of life of affected patients [4]. In the UK, it is reported that there has been an increase in incidence of approximately 25% since 1985 [6,7]. The pathogenesis of human penile SCC (hPSCC) remains unclear; lack of circumcision, phimosis, cigarette-smoking and obesity have been widely discussed as potentially contributing to its development.…”
Section: Introductionmentioning
confidence: 99%
“…The treatment of penile cancer is often mutilating, and may negatively impact on the quality of life and sexual functioning of patients . The treatment cost per case of penile cancer is substantial, and comparable to that of other urological cancers …”
Section: Introductionmentioning
confidence: 99%
“…11,12 The treatment cost per case of penile cancer is substantial, and comparable to that of other urological cancers. 13 Strong risk factors for penile cancer include phimosis and chronic inflammatory conditions. 14 The increased risk of penile cancer among men with phimosis is associated with lichen sclerosis or inadequate penile hygiene, smegma retention and thus infection.…”
Section: Introductionmentioning
confidence: 99%